FPGA-Based Implementation Nonlinear Backstepping Control of a PMSM Drive - Badre Bossoufi; Mohammed Karim; Ahmed Lagrioui; Mohammed Taoussi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2014)
In this paper, we present a new contribution of FPGAs (Field-Programmable Gate Array) for control of electrical machines. The adaptative Backstepping control approach for a permanent magnet synchronous motor drive is discussed and analyzed. We present a Matlab&Simulink simulation and experimental results from a benchmark based on FPGA.  The Backstepping technique provides a systematic method to address this type of problem. It combines the notion of Lyapunov function and a controller procedure recursively. First, the adaptative and no adaptative Backstepping control approach is utilized to obtain the robustness for mismatched parameter uncertainties. The overall stability of the system is shown using Lyapunov technique. The simulation results clearly show that the proposed scheme can track the speed reference. Secondly, some experimental results are demonstrated to validate the proposed controllers. The experimental results carried from a prototyping platform are given to illustrate the efficiency and the benefits of the proposed approach and the various stages of implementation of this structure in FPGA.DOI: http://dx.doi.org/10.11591/ijpeds.v4i1.4645